Analisis efektivitas peran audit internal atas pengendalian persedian barang dagang pada PT. Aneka Ragam Engeneering - Siti Aisyah; Ridho Gilang Adiko; Mifta Pramudita Marwan (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
Internal control and internal audit are very important things to be done consistently by a company. With the existence of an internal audit, it is expected to be able to assess, see, and measure whether the internal control in the company has been running effectively or not. Inventory is a company asset that is at high risk of loss, damage, and is vulnerable to excess or shortage of inventory. PT. Aneka Ragam Engeneering is one of the manufacturing companies engaged in Engineering, Construction & Manufacturing which is located at Jl. Palembang No.35, Kel. Downstream Pandau. The purpose of this study was to find out why internal audit at PT. Aneka Ragam Engineering is still not effective in controlling the company's merchandise inventory, where it turns out that there are still some problems in controlling the company's merchandise. This research approach uses a descriptive approach and uses qualitative methods.